Hematology of Osphronemus gouramy Fed with Turmeric (Curcuma domestica Val) and Maggot (Hermetia illucens) Enriched Pellets - Daniel Nainggolan; Morina Riauwaty; Henni Syawal (Jurnal Perikanan dan Kelautan, 2026)
Osphronemus gouramy is a widely cultivated fish because it has economic value in the community and is high in protein. The addition of turmeric powder and maggot flour can increase the nutritional value of gurami fish feed. The study was conducted from January to May 2025 at the Parasite and Fish Disease Laboratory, Faculty of Fisheries and Marine Sciences, Universitas Riau. The objective of this study was to determine the effect of adding turmeric powder (Curcuma domestica Val) and maggot meal (Hermetia illucens) to the feed on the hematology of O. gouramy infected with Aeromonas hydrophila. The method used was an experiment with a completely randomized design with one factor and five treatments, namely Kn (feeding without the addition of maggot meal and turmeric powder without infection with A. hydrophila), Kp (feed without maggot meal and turmeric powder, infected with A. hydrophila), P1, P2, and P3 (feed with 0.9 g/kg turmeric powder and 20, 30, and 40 g/kg maggot meal, then infected with A. hydrophila). Feeding was carried out three times a day to satiation. On day 32, the fish were infected with A. hydrophilla at a density of 108 CFU/mL, 0.1 ml. The results showed that feed containing 0.9 g/kg turmeric powder and 30 g/kg maggot meal resulted in a total erythrocyte count of 1.91×106 cells/mm, hematocrit of 38%, hemoglobin 9.06 g/dL, total leukocytes 11.15x10⁴ cells/mm³, phagocytosis activity 25.66%, absolute weight gain 11.71 g/fish, specific length 5.74 cm, and survival rate 80%. Water quality during the study was as follows: temperature ranging from 27.6-29°C, pH 6.51-7.61, and DO 4.6-5.9 mg/L. Based on the data, it can be concluded that the addition of turmeric and maggots to pellets can increase the growth and immunity of O. gouramy infected with A. hydrophila